Produção da biomassa de Pleurotus albidus por fermentação submersa para elaboração de barras de cereais - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
In recent years the search for foods that promote quality of life and expectation of consumers has grown worldwide. Species of Pleurotus cater to this trend because they are considered foods of high nutritional potential. This study aimed to evaluate the in vitro conditions of production and the nutritional properties of Pleurotus albidus in order to develop cereal bars. Initially we evaluated the influence of culture conditions on solid medium and physicochemical parameters in submerged fermentation to produce mycelial biomass. The results showed that the mycelial growth was similar in all culture media in the absence of light, however, in the presence of light growth in malt extract agar and malt extract agar with yeast extract was statistically superior compared with others. In submerged fermentation sucrose, fructose and maltose were the carbon sources that most favored the production of biomass, 7.28 g.L-1, 7.07 g.L-1, 6.99 g.L-1, respectively, and the best result was obtained with extract of yeast (7.98 g.L-1) as nitrogen source. The factorial design used to evaluate the influence of sucrose and yeast extract, agitation speed and pH indicated that all variables significantly influenced the production of biomass, especially the concentration of sucrose. The maximum biomass production (9.81 g.L-1) was in media containing sucrose (30.0 g.L-1), yeast extract (2.5 g.L-1), pH 7.0 and agitation speed (180 rpm). Biomass exhibited no microbial contamination or toxicity in the brine shrimp¸ and showed a reduction in antioxidant capacity with 28% DPPH. In nutritional quality, biomass indicated total carbohydrate 50.7%, 20.41% protein, 18.55% crude fiber, 8.18% ash, 2.66% fat and 308.34 Kcal. Potassium was the most abundant macromineral, followed by phosphorus, sodium and magnesium, with 17.13 g.kg-1, 12.31 g. Kg-1 3.52 g.Kg-1 and 2.06 g.Kg-1 respectively, while zinc (57.99 mg.Kg-1), iron (28.82 mg.Kg-1) and copper (3.97 mg.kg-1) were as trace minerals in greater quantities. All essential amino acids were detected in the biomass, being the most abundant leucine, lysine and valine at levels of 0.91 g.100g-1, 0.78 g.100 g-1 and 0.73 g.100 g-1, respectively. Aspartic acid (1.31 g.100 g-1), glutamic acid (1.14 g.100 g-1), alanine (1.12 g.100 g-1) and arginine (1.01 g.100 g-1) stood out in relation to non-essential amino acids. In relation to microbiological quality of the three formulations prepared cereal bars with different P. albidus biomass concentration (0%, 4% and 8%) were considered safe for human consumption. The addition of biomass of P. albidus in cereal bars increased the content of fiber, carbohydrates and minerals. The mean values of the attributes evaluated were not statistically different among the three formulations and all had acceptability index above 70%. The cultivation conditions provided the production of mycelial biomass of P. albidus for developing cereal bars, food product with nutritional and sensory qualities suitable for consumption, subject to technology transfer to industry and consequently a new alternative source of incomes.
Keywords: Pleurotus albidus; Fermentação submersa; Composição nutricional; Barras de cereais; Pleurotus albidus; Submerged culture; Nutritional composition; Cereal bars; CIÊNCIAS BIOLÓGICAS